Exploring the Similarities and Differences among the Kinds of Curriculum Implemented in Indonesian Schools - Kalayo Hasibuan; Erlinda Agustina (The Progress: Journal of Language and Ethnicity, 2023)
This paper explores the similarities and differences among the kinds of the curriculums such as the School-Based Curriculum, 2013 Curriculum and the Freedom to Learn Curriculum that have been implemented in Indonesian schools. Their similarities and differences comprise the conceptual or theoretical frameworks, the instructional procedures and the assessment at schools in Indonesia. The curriculum as a determinant of educational success must be responsive to all contemporary challenges and innovations. The 2013 Curriculum and the Freedom to Learn Curriculum, the so called “Merdeka curriculum” are currently being implemented. The Indonesian government has adjusted the changes to the curriculum as much as possible to meet the educational goals expected in this digital era. The objective of this article is to compare the kinds of the implemented curriculums in Teaching English as A Foreign Language (TEFL) based on the basic frameworks, targeted competencies, curriculum structure, learning, assessment, teaching tools, and curriculum tools.